THE ROLE OF DATABASE MARKETING IN THE OPERATIONALIZATION OF THE SERVICES RELATIONSHIP MARKETING - Luigi DUMITRESCU; Mircea FUCIU (Management & Marketing, 2010)
The relationship marketing aims the construction of a durable relation between the enterprise and the final client, identified at an individual level. The particular part of the relationship marketing has two main concepts: individuality and the relation. This paper presents the concepts of relationship marketing, database marketing and geomarketing. We present the importance of implementing a marketing database in a service providing enterprise and its implications on one hand for the client and on the other hand for the enterprise. The paper point out the marketing database instruments and the advantages for the elements of the marketing mix. The implementation of a marketing database will aid the enterprise to better target and attract the client, to transform them into loyal consumers and in the same time it can help refresh the image of the enterprise.